Estratégias sustentáveis de projeto para a infraestrutura urbana de loteamentos de interesse social - Grub, Julian (2010)
This assignment proposes a set of sustainable strategies of project, focused on the urbanization of land subdivisions of social interest, in order to assist in urban infrastructure in its various project networks. A bibliographic study was performed taking into consideration alternative infrastructure networks with lower environmental impact and the case study of a subdivision of social interest, evaluating aspects such as urban inclusion and residents´ satisfaction. The case study concerns a project of a popular subdivision located in the city of Portão, Rio Grande do Sul, implemented with funds from a housing subsidy program called Pró-Moradia and from municipal resources. A mirror of an urban reality, a model of a land subdivision of social interest was sought in the case study, resorting to the morphology adopted, the regular trace. Failures in the infrastructure implementation could be observed in the physical and environmental issue of the subdivision, due to the lack of planning, lack of more humanized design criteria and turned to the use of the public space, influencing the residents´ quality of life. Finally, an example of a subdivision of social interest is presented in order to put into practice the concepts and investigations carried out through this work, launching under the sustainable aspects, strategies of urban design. It is believed that the research, here presented, will raise discussions about the subject and provide subsidies to urbanization projects relating to human settlement, considering low environmental impact and quality of life